Hubungan Kehamilan Usia Dini Dengan Kejadian Bayi Lahir Prematur - Bali, Andi Azizah Nabila Tenri; Arfah, Arni Isnaini; Kamaluddin, Irna Diyana Kartika; Nulanda, Mona; Darussalam, Andi Husni Esa (Journal of Telenursing (JOTING), 2024)
This study aims to determine the relationship between early pregnancy and the incidence of premature births and also the relationship between the incidence of premature births and LBW (Low Birth Weight Babies) in 2019-2023. The method used in this study is quantitative research with a descriptive research design conducted at RSIA Sitti Khadijah 1 Makassar in May 2024. This sample uses total sampling. The results of the study showed that out of 655 samples, 47 samples were taken that met the inclusion criteria, so that from the 47 samples, the prevalence of premature births from early mothers at RSIA Sitti Khadijah 1 Makassar in 2019-2023 was 21.3% for the extreme premature category, 29.8% for the very premature category, and 48.9% for the moderate to late premature category. The prevalence of BBLR (Low Birth Weight Babies) at RSIA Sitti Khadijah 1 Makassar in 2019-2023 was 61.7% for the low birth weight category and 38.3% for the very low birth weight category. The results of the bivariate test of early pregnancy with the incidence of premature birth obtained a p-value of 0.084 and the results of the bivariate test of the incidence of premature birth with BBLR (Low Birth Weight Babies) obtained a p-value of 0.003. The conclusion of this study is that there is no relationship between early pregnancy and the incidence of premature birth. There is a relationship between the incidence of premature birth and BBLR (Low Birth Weight Babies). Keywords: BBLR (Low Birth Weight Babies), Early Pregnancy, Incidence Of Premature Birth